Human Resources Competencies in the Marine and Fisheries Sector: An Review - Gede Agus Pratama; Sang Ayu Made Putri Suryani; I Nengah Muliarta (Formosa Journal of Sustainable Research, 2023)
Increasing human resource competency is one of the keys to advancing the maritime and fisheries sector in Indonesia. Increasing human resource competency must be balanced with standardization, competency of teaching staff and good infrastructure. This research aims to determine the importance of competency-based learning to improve the quality of competent human resources to advance the marine and fisheries sector. The method used in this research is the literature review method. The results of this research are that there are several important factors in improving the competency of marine and fisheries         human            resources,      namely: standardization, curriculum, teaching staff and good infrastructure. If these four factors are met then it can improve the knowledge, skills and attitudes of marine and fisheries human resources